FAKTOR PENGHAMBAT SISTEM MANAJEMEN KESELAMATAN KONSTRUKSI PADA PROYEK JALAN PELABUHAN TELUK TAPANG - Revi Yuliana; Nafryzal Carlo; Dwifitra Y. Jumas; Lusi Utama; Eva Rita (Rang Teknik Journal, 2026)
The construction industry in Indonesia is experiencing rapid growth, yet the improvement in construction project management to minimize construction accidents is not commensurate with the expansion. According to data from the Social Security Administration for Manpower in Sumatra and Riau, there were 31,801 workplace accidents in 2021, with 216 cases involving construction workers, predominantly occurring at job sites. This is largely attributed to the frequent neglect of implementing the Construction Safety Management System (SMKK) on construction projects, which inherently pose high risks and accident rates. This research aims to identify the inhibiting factors in the implementation of SMKK during the construction phase, based on The Ministry of Public Works and Housing Regulation No. 10 of 2021. A qualitative descriptive method was employed, involving interviews with 11 key informants including Commitment Making Official of planner, Commitment Making Official of execution, Commitment Making Official of supervisor, Consultant of Planner, Contractor of construction, Consultant of Inspection and tender committee. The study identified four main barriers: inadequate awareness among workers regarding safety priorities, infrequent presence of HSE personnel from consulting supervisors until project completion, lax oversight by Top Management, and ineffective outcomes following internal audits, failing to achieve expected improvements.Keywords: Inhibiting Factor, Construction Accident, Construction Project, Inhibiting Factor, The Ministry of Public Works and Housing Regulation No. 10 Year 2021, SMKK